REFORMULASI MANAJEMEN PENDIDIKAN DALAM PENINGKATAN MUTU PESANTREN SALAF DI KABUPATEN PRINGSEWU LAMPUNG - AMIRUDIN, AMIRUDIN (Universitas Islam Negeri Raden Intan Lampung, 2015)
Management is one important components in educational institution or other institutions. Bad management mechanism will greatly affect the quality or out-putnya. To achieve these objectives effectively and efficiently, it is necessary to include professional management.The research aims to find out how reformulation in education management in an effort to improve the quality as well as knowing what constraints experienced in the reformulation of management education in improving the quality of Nurul Huda Pringsewu.The method used in this research is descriptive and qualitative data sources you want to use is the primary and secondary data sources. The primary data source in this study are those directly involved in Nurul Huda Pringsewu. Secondary data source in this study is documentation, bureaucratic systems and interviews.Based on the above analysis, reformulation of management at boarding Nurul Huda seen from the development of the form and its educational system. Likewise, the curriculum used, always follow the policy of the government in implementing the curriculum in schools or madrassas. This development is based on the interest of students and the public on the development and change of management education in schools Keywords: Reformulation of Management, Education and Quality Pesantren